Dynamic analysis of taut mooring systems - Lim, Wan Yu. (2013)
This report is part of an ongoing study by two final year students (Rachel Amanda Netto and the author). The aim of the study is to investigate the effects of various design parameters on the dynamic response of taut mooring system using the simulation program OrcaFlex. Taut mooring system is increasingly applied in offshore deepwater oil drilling platform. Yet, the polyester rope taut leg mooring is a fairly new system that has been developed, hence warranting further study in the area. As the wide review of literature does not have certain important studies such as effect of water depth and influence of random variables on the mooring line.